2007
DOI: 10.1103/physrevb.76.064512
|View full text |Cite
|
Sign up to set email alerts
|

Weak-couplingd-wave BCS superconductivity and unpaired electrons in overdopedLa2xSrxCu

Abstract: The low-temperature specific heat (SH) of overdoped La 2−x Sr x CuO 4 single crystals (0.178 x 0.290) has been measured. For the superconducting samples (0.178x 0.238), the derived gap values (without any adjusting parameters) approach closely onto the theoretical prediction ∆ 0 = 2.14k B T c for the weak-coupling d-wave BCS superconductivity. In addition, the residual term γ(0) of SH at H = 0 increases with x dramatically when beyond x ∼ 0.22, and finally evolves into the value of a complete normal metallic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
73
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 40 publications
16
73
0
Order By: Relevance
“…From figure 1 and table 1 we can see the A essentially decreases with decreasing doping. Thus this suggests that the ∆ 0 becomes larger towards underdoping [10]. Actually it has been shown that in the underdoped region, the ∆ 0 quantitatively tracks the pseudogap in the normal state [9].…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…From figure 1 and table 1 we can see the A essentially decreases with decreasing doping. Thus this suggests that the ∆ 0 becomes larger towards underdoping [10]. Actually it has been shown that in the underdoped region, the ∆ 0 quantitatively tracks the pseudogap in the normal state [9].…”
mentioning
confidence: 90%
“…-We have performed the lowtemperature SH measurement in LSCO throughout the entire superconducting phase diagram [9][10][11]. The samples used for the study were single crystals prepared by the traveling-solvent floating-zone method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been concluded that the superconductivity in overdoped LSCO is pure and that the electronic state is inhomogeneous [2]. For dirty d-wave superconductors, on the other hand,  0 is proportional to HlnH [6].…”
Section: Resultsmentioning
confidence: 99%
“…For hole-doped La 2-x Sr x CuO 4 (LSCO), it has been suggested from the magnetic susceptibility measurements that both the superconducting (SC) transition temperature, T c , and the SC volume fraction decrease markedly with increasing x in the overdoped regime [1]. The low-temperature specific heat measurements have revealed the existence of a finite value of the Sommerfeld constant in the SC ground state [2]. In addition, from the magnetization-hysteresis-loop measurements, a so-called second magnetization peak has been observed in the overdoped regime, indicating the enhancement of the vortex pinning [3].…”
Section: Introductionmentioning
confidence: 99%